Recuerdo : a novel - Hidalgo, Cristina Pantoja (Quezon City, Philippines : University of the Philippines Press, 1996)
Recuerdo is an epistolary novel consisted of messages sent through email. The messages all came from Amanda, a middle-aged widow, to her daughter Marisa, a university student. Amanda is in Bangkok while Marisa is in Manila. Writing letters is Amanda's way of sorting out her life and helping Marisa understand their family' past. Amanda use her own mother's (Isabel) stories in many of these letters.
Letter 1. Revisiting old haunts -- Letter 2. El chino tomas and la leonor -- Letter 3. Don lorenzo and la chiquita -- Letter 4. A short tale of two cities -- Letter 5. They cam in the night -- Letter 6. Inya lake hotel -- Letter 7. La pobre asuncion -- Letter 8. Oh, look at all the lonely people -- Letter 9. Baguio on my mind -- Letter 10. Gypsies -- Letter 11. Maestra cresing -- Letter 12. Carl -- Letter 13. Lorenzo the martyr -- Letter 14. Asia pattaya hotel -- Letter 15. Back in manila -- Letter 16. Carl takes charge -- Letter 17. Soeur stella -- Letter 18. A love story -- Letter 19. On being given the world -- Letter 20. Paz -- Letter 21. The third in the line -- Letter 22. On coming home -- Letter 23. Sally's continuing misfortunes -- Letter 24. The family's first ocw -- Letter 25. The missing ancestor -- Letter 26. Inya lake hotel -- Letter 27. The old maid -- Letter 28. The letter -- Letter 29. Isabel's childhood -- Letter 30. Alicia -- Letter 31. Before the war -- Letter 32. The white savior -- Letter 33. Nikki -- Letter 34. War -- Letter 35. The accident -- Letter 36. There is no curse... -- Letter 37. Holiday inn -- Letter 38. My leap of faith -- Letter 39. Quezon City.
Keywords: LITERARY FICTION